3D interconnected nitrogen-self-doped carbon aerogels as efficient oxygen reduction electrocatalysts derived from biomass gelatin. Issue 69 (4th December 2019) - Yang, Haoqi; Kou, Shuqing; Li, Zhiyuan; Chang, Zhiyong; Wang, Mi; Liu, Zhenning; Lu, Guolong
Abstract : Development of efficient metal-free electrocatalysts derived from biomass with high activity towards oxygen reduction reaction (ORR) has gained significance attention due to their low manufacturing cost, environmental friendliness and easy large-scale production. Abstract : Development of efficient metal-free electrocatalysts derived from biomass with high activity towards oxygen reduction reaction (ORR) has gained significance attention due to their low manufacturing cost, environmental friendliness and easy large-scale production. Hence, we present a facile method to prepare nitrogen-self-doped carbon aerogels (NSCAs) with a three-dimensional (3D) interconnected porous structure and large surface area. The sample is prepared via high-temperature pyrolysis using gelatin as precursor and sodium chloride (NaCl) as sacrificial template. The obtained NSCA-800 catalyst shows excellent ORR performance in O2 -saturated alkaline electrolyte, which is comparable to a commercial Pt/C catalyst, in terms of its onset potential (0.92 V vs. RHE), half-wave potential (0.77 V vs. RHE), and limited current density (5.31 mA cm −2 ). Particularly, the NSCA-800 catalyst exhibits outstanding long-term stability, its ORR kinetic current still retains 95.7% after a continuous 4 h test while that for commercial Pt/C retains just 74.3%. The sustainable biomass gelatin is a promising precursor for the development of carbon materials as effective ORR catalysts.